Perceived likelihood of using HIV Pre-Exposure Prophylaxis Medications Among Young Men Who Have Sex With Men - Mustanski, Brian (2013)
Pre-exposure prophylaxis (PrEP) is a new strategy for reducing the risk of HIV infection; however, questions about the likelihood of use remain. As part of an ongoing longitudinal study of YMSM, interest in PrEP use under various conditions of side-effects, dosing, and effectiveness were assessed. Participants aged 16–20 living in Chicago and the surrounding areas were recruited beginning December 2009, using a modified form of respondent driven sampling. A cross-sectional sample of 171 HIV negative YMSM interviewed approximately 6 months after initial enrollment was analyzed. This sample was somewhat interested in adopting PrEP as an HIV prevention strategy, particularly if the dosing and side-effects burden was low and the perceived benefits were high. PrEP interest was unrelated with drug use and number of sexual partners, but negatively correlated with number of unprotected anal sex acts. The scale was positively associated with intentions for use in specific risk situations.